Production of polysaccharide hydrolases in the genus Rhizopus - Kolarova, N; Augustín, J (Folia microbiologica, 2001)
Polysaccharide hydrolase activity was assayed in a group of 28 selected Rhizopus strains. The production of lichenases, mannanases, cellulases, xylanases, amylases and pullulanases was demonstrated using the gel-testing method during growth of the strains on suitably meshed polysaccharide gels.
Keywords: Fermentation; fermentace; Xylosidases; Rhizopus; xylosidasy; polysacharidy; Polysaccharides